(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
The coronavirus related crisis affected severely all aspects of life and judiciary is no exception. The world has been confronted with new challenges. New circumstances have created significant impact on the functioning of access to justice. New ways of administrating the legal system were introduced in the last decade, allowing for the use of the means of electronic communication, reducing certain stages of court procedures, opting for solutions for peaceful dispute settlement and promoting out-of-court dispute resolution. However, the coronavirus caused, beyond any doubt, severe delays in court proceedings and even shut down courts in some European Union Member States, Croatia included. Thus, additional efforts were required in order to ensure remote justice to citizens and businesses. More importantly, it called for a swift response, issuing and applying emergency measures, to safeguard the right to access courts and provide for effective administration of justice. The paper thus seeks to explore the ways in which European Union Member States responded to emerging challenges and the consequences these challenges had on administration of justice. Croatian example will be introduced specifically due to obvious struggles in handling the coronavirus caused difficulties in national judiciary system. Along with the analysis of measures taken, there are several questions, which need to be answered. What was the level of readiness of the Member States’ judiciaries for providing justice by means of electronic communications, with Croatia in focus? What are the effects of measures taken in Croatian judiciary system? Should it be left to the courts or other competent bodies to take actions on a case-to-case basis in order to provide the necessary protection of procedural rights to parties? In terms of the effect of the emergency measures, do they allow for the same or similar quality of remote justice? In conclusion, the paper will try to answer the aforementioned questions, deliberate on the efficiency of measures taken in response to the coronavirus crisis, with Croatia in focus and possibilities of future improvements.